Surface Treatment of Acetabular Cups with a Direct Deposition of a Composite Nanostructured Layer Using a High Electrostatic Field - Pokorný, Marek; Suchý, Tomáš; Kotzianová, Adéla; Klemeš, Jan; Denk, František; Šupová, Monika; Sucharda, Zbyněk; Sedláček, Radek; Horný, Lukáš; Králík, Vlastimil; Velebný, Vladimír; Čejka, Zdeněk (Molecules (Basel, Switzerland), 2020)
A composite nanofibrous layer containing collagen and hydroxyapatite was deposited on selected surface areas of titanium acetabular cups. The layer was deposited on the irregular surface of these 3D objects using a specially developed electrospinning system designed to ensure the stability of the spinning process and to produce a layer approximately 100 micrometers thick with an adequate thickness uniformity. It was verified that the layer had the intended nanostructured morphology throughout its entire thickness and that the prepared layer sufficiently adhered to the smooth surface of the model titanium implants even after all the post-deposition sterilization and stabilization treatments were performed. The resulting layers had an average thickness of (110 ± 30) micrometers and an average fiber diameter of (170 ± 49) nanometers. They were produced using a relatively simple and cost-effective technology and yet they were verifiably biocompatible and structurally stable. Collagen- and hydroxyapatite-based composite nanostructured surface modifications represent promising surface treatment options for metal implants.
Keywords: Spectrum Analysis, Raman; electrospinning; Ramanova spektroskopie; nanofibers; nanostruktury; Static Electricity; titanium implant; Nanostructures; collagen composite; hydroxyapatite; statická elektřina